Pengembangan Media Interaktif Berbasis Adobe Flash CS6 untuk Meningkatkan Hasil Belajar Siswa Pembelajaran Pendidikan Pancasila Kelas IV SD Muhammadiyah Ngluwar - Amanda Kurnia Rahmadini; Ari Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to develop interactive learning media based on Adobe Flash CS6 to improve feasible, practical, and effective student learning outcomes. The research and development method is Research and Development with the ADDIE model. Based on the study, it shows that interactive learning media based on Adobe Flash CS6 has been developed as a learning medium for Pancasila education. The results of the media expert validation test obtained a score of 81% (very feasible) and material experts 80% (feasible). Based on the practicality test, the assessment of teacher responses obtained a percentage of 80% (practical) and students 93.7% (very practical). The effectiveness of the learning media was determined by the Paired Sample t-Test test, obtained pretest and posttest results have a Sig. (2-tailed) value of 0.000, so the Sig. (2-tailed) value <0.05. These results indicate a difference between the pretest and posttest results. Thus, the interactive learning media based on Adobe Flash CS6 that has been refined based on input from validators and experts is considered feasible, practical, and effective as a learning medium for Pancasila education.